Prevention of Campylobacter jejuni K49/4 adhesion to porcine small intestine cell line PSI cl1 using different plant extracts: Preprečevanje adhezije Campylobacter jejuni K49/4 na celično kulturo prašičjih črevesnih celic PSI cl1 z uporabo različnih rastlinskih ekstraktov - Šikić Pogačar, Maja; Klančnik, Anja; Smole Možina, Sonja; Mičetić Turk, Dušanka (Acta Medico-Biotechnica, 2021)
Purpose: The aim of this study was to investigate the in vitro anti–adhesive properties of chemically characterized ethanolic extracts from waste Pinot noir grape (GSS) skins and seeds, olive tree leaves (OE), thyme (Thymus vulgaris) prior to (TE) and its residue after (TE–R) hydrodistillation of the essential oil, as well as Alpinia katsumadai ethanolic seed extracts (SEE) and its hydrodistillation residue (hd- SEE–R) against the pig small intestine epithelial cell line, PSI cl1. Methods: Using PSI cl1, the anti– adhesion activities of these extracts, which normally represent "waste material" and by–products from the agro– food industry, were determined. Initially, the anti–Campylobacter jejuni and cytotoxic activities of GSS, TE, TE–R, SEE and hdSEE–R were determined to avoid any interference in the anti– adhesion assay being used. Results: The A. katsumadai extracts showed the strongest anti–adhesive activities against C. jejuni K49/4. When using TE and TE–R, C. jejuni adhesion to PSI cl1 cells was inhibited by almost 30% over a large concentration range of extracts. GSS extracts had the lowest impact on the adhesion rate of C. jejuni to PSI cl1 cells. Conclusion: Our findings suggest that agro–food waste material and many by–products from the agro–food industry represent sources of bioactive phytochemicals that are effective at low concentrations and could be used as therapeutic agents to prevent bacterial adhesion. This represents a step towards the application of new innovative strategies to control Campylobacter contamination and infection in the food chain. We suggest that not only plant extracts, but also waste material and agro–food industry by–products can be used as promising novel therapeutic agents with possible medical and industrial applications.